Social Media Tools and Platforms in Learning Environments - White, Bebo; King, Irwin; Tsang, Philip (Springer eBooks., 2011)
Online social media have transformed the face of human interaction in the 21st century. Wikis, blogs, online groups and forums, podcasts, virtual worlds, and social tagging are but a few of the applications enabling innovative behaviors that support acquisition, access, manipulation, retrieval, and visualization of information. It is, therefore, no surprise that educational practitioners and theorists have begun to explore how social media can be harnessed to describe and implement new paradigms for communication, learning, and education. The editors goal in publishing this book was to identify original research on the application of online social media and related technologies in education as well as emerging applications in Web technologies that could provide and shape future educational platforms. The selected contributions deal with questions such as how social media can truly enrich and enhance learning and teaching experiences in ways not otherwise possible; how learning can be integrated in a distributed and ubiquitous social computing environment; or what theories, paradigms, and models are applicable for the support of social computing in education. Researchers in education or educational software will find interesting and sometimes provocative chapters on paradigms and methodologies, virtual and mobile learning spaces, and assessment and social factors. Practitioners in these fields will benefit from an additional section devoted to case studies and first experience reports.